Medium of instruction policy change in Sudan : its impact on the English language proficiency of Sudanese medical students - Bakhit, Mohamed Agaban (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The decline of English language standards among Sudanese university students and graduates has become one of the issues, which has preoccupied public opinion in Sudan. Media, employers, parents, and school and university teachers are concerned about the falling standards of English language among Sudanese students and graduates. Therefore, the objective of this study is to investigate the impact of the medium of instruction on the English language proficiency of Sudanese medical students. Four instruments were used to collect data for this study. The first was a writing test, which aimed at assessing the English language proficiency of two groups of students; namely a group that studied through the medium of English, and a group that studied through the medium of Arabic. The English-medium students were second year medical students at Khartoum University, Sudan, while the Arabic-medium students were second year medical students at Gezera University, Sudan. A sample of 151 students was chosen from the former group, and a sample of 155 students was chosen from the latter group. The second instrument was a survey questionnaire to elicit students' perceptions on the effect of using Arabic as a medium of instruction on the English language proficiency of Sudanese medical students. The questionnaire was administered to 201 participants from both Khartoum University and Gezera University. The third instrument was a survey questionnaire for teachers, academicians, employers, and language policy makers to elicit their perceptions on the effect of using Arabic as a medium of instruction on the English language proficiency of Sudanese medical students and their perceptions on factors that have led to the deterioration of English language standards in Sudan. The questionnaire was administered to 30 academicians and 30 English language teachers working at Khartoum and Gezera Universities respectively, 10 employers working at University of Khartoum, Ministry of Health and Ministry of Education, and 6 language policy makers working at University of Khartoum and Ministry of Education. The fourth instrument was an interview to obtain detailed information and rich data about the impact of using Arabic as a medium of instruction on the English language proficiency of Sudanese medical students. It was also used to obtain insights on factors contributing to the deterioration of English standards among these students. The results show that using Arabic as a medium of instruction has an adverse effect on the English language proficiency of Sudanese medical students. The results also indicate that low wages and salaries, lack of motivation on the part of students, syllabuses which do not meet the needs of students, lack of adequate training for teachers, poor English proficiency among university new entrants, and the problem of large classes were the other factors responsible for the deterioration of English standards among Sudanese medical students.